Diversity of butterflies in the tropical wetland of Kayan-Sembakung Delta, North Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Harmonis, Rahim A, Hidayat HA, Saud OR, Wilujeng M, Sampe R, Kartika KF, Aminudin, Butar TB. 2022. Diversity of butterflies in the tropical wetland of Kayan-Sembakung Delta, North Kalimantan, Indonesia. Biodiversitas 23: 3303-3312. Butterflies, which belong to the order Lepidoptera, are considered superior biological indicators to evaluate environmental conditions in various types of habitats due to their high richness in biodiversity, short generation time, good movement, and high sensitivity. Since butterflies produce various benefits for the ecosystem, their conservation currently receives significant attention in order to improve human well-being. However, there is still limited research about butterfly diversity in tropical wetlands, especially in Borneo (Kalimantan) Island. Herein, we identify the diversity of butterflies found in the Kayan-Sembakung Delta, North Kalimantan, which is still unexplored so far. The area was dominated by mangroves, peat swamps, and brackish swamps. The research locations inside the Kayan-Sembakung Delta were divided into 20 groups. The specimen was collected by an aerial insect net and bait traps. The diversity index, taxonomy structure, and domination index were further investigated. The results showed that the highest individuals (69) and species (36) had been found in Pembeliangan. Altogether, we found 608 individuals of 92 species in the areas studied. Among others, the family of Nymphalidae was noted as the most dominant. We stated that the diversity of butterflies was also influenced by the type of habitat, as it could be found at the peat swamp forest where the highest species were found. In the meantime, some unique species have been found in the Kayan-Sembakung Delta, including Arhopala overdijkinki, Hypolycaena thecloides, Drupadia johorensis, Idea leuconoe, and Polyura jalysus. The results of this study are expected to give more information for future management and conservation of the wetland areas, especially in the Kayan-Sembakung Delta.
Keywords: Butterfly diversity, conservation, Lepidoptera, unique species, wetland